The Role of HDACs and HDACi in Cartilage and Osteoarthritis - Zhang, He; Ji, Lu; Yang, Yue; Zhang, Xiaoning; Gang, Yi; Bai, Lunhao (Frontiers in Cell and Developmental Biology, 2020)
Epigenetics plays an important role in the pathogenesis and treatment of osteoarthritis (OA). In recent decades, HDAC family members have been associated with OA. This paper aims to describe the different role of HDACs in the pathogenesis of OA through interaction with microRNAs and the regulation of relevant signaling pathways. We found that HDACs are involved in cartilage and chondrocyte development but also play a crucial role in OA. However, the distinct HDAC mechanism in the pathogenesis and treatment of OA require further investigation. Furthermore, HDAC inhibitors (HDACi) can protect cartilage from disease, which may represent a potential therapeutic approach against OA.